Factors contributing to maternal mortality at public health institutions at the Sekhukhune District Limpopo Province, South Africa - Sioga, Tshimangadzo Ronald (My University, 2021)
Background: Maternal mortality is a significant public health problem worldwide, and is a vital indicator of the functioning of a health system. The South African maternal mortality ratio is higher than other countries with same economic growth, despite people having free access to maternal health. How to develop relevant policies and programmes to reduce maternal mortality factors contributing to maternal mortality was investigated. Aims of the Study: To investigate the factors contributing to maternal mortality in public health institutions in the Sekhukhune District, Limpopo Province, South Africa. Methods: A quantitative, retrospective study was undertaken where 138 medical records of maternal mortality cases reported between 2013 to 2017 were reviewed. A simple random sampling method was used to select files that met the selection criteria from seven hospitals in the Sekhukhune District, Information was collected on maternal demographics and health service-related characteristics, including age, marital status, parity, antenatal care utilisation of services and delivery type. Inferential data were analysed using the student t-test and SPSS version 25. Results: The mean age of the women involved in this study was 30 years, with a standard deviation of 5.7. All the women who participated in the study were black African. The majority of maternal mortality occurred in hospital. The women in the majority of maternal mortality cases were unemployed, at 93.5%, while most of the maternal mortality cases involved single women (71%).The women involved in these maternal mortality cases booked their ANC care and the major health provider was a professional nurse (58.0%), while 57.2% of the participants attended their ANC at primary healthcare facilities. Most of the maternal deaths occurred after delivery (58.7%) and, in most deliveries, the Partogram was not used (66%). HIV testing occurred in 99% of the maternal mortality cases. The causes of maternal mortality were both direct (71.0%) and indirect (23.9%) causes. The leading cause of maternal mortality was direct haemorrhage (33%), followed by eclampsia (27%) and infection (16%). The leading indirect cause was respiratory causes (22%) and retro viral disease (RVD) (9%). The personal factor that contributed most to maternal mortality was delay in seeking help (62%). v Conclusion and Recommendations: The personal factor, delay in seeking medical help by the women, contributed to maternal mortality and it was further concluded that the majority of maternal mortality cases did not occur as a result of any complications in ANC and delivery. It is recommended that the training of healthcare providers in the utilisation of the Partogram be implemented to improve skills in the management of haemorrhage and eclampsia. Furthermore, the management of complications needs to be strengthened through a multi-sectorial approach.
Theses ( MPH.) -- University of Limpopo, 2021
Keywords: Contributing factors; Maternal mortality; Public Health Institutions; Mothers -- Mortality; Health facilities -- South Africa -- Limpopo; Hemorrhage; Eclampsia